KEPASTIAN HUKUM SMART CONTRACT DALAM PERSPEKTIF HUKUM PERDATA - Sakirman; Ma'ruf Akib; Wahyudi Umar (CV Rewang Rencang, 2024)
Legal certainty in the application of smart contracts in the perspective of civil law is an important issue in the digital era. Smart contracts, which are computer code that automatically executes agreements, face challenges in meeting the legal requirements of traditional contracts. Previous research shows that while smart contracts offer transparency and efficiency, they often do not meet the validity criteria set out in civil law, as expressed by Herian and Abidin. In addition, there is an urgent need for clearer regulation regarding the legal status of smart contracts so that they can be integrated with existing legal systems, as discussed by Onufreiciuc and Stănescu. Therefore, this study aims to explore the legal certainty of smart contracts and their implications for civil law, as well as provide recommendations for better arrangements in the future.